2007
DOI: 10.1002/ajpa.20717
|View full text |Cite
|
Sign up to set email alerts
|

Epiphyseal union at the innominate and lower limb in a modern Portuguese skeletal sample, and age estimation in adolescent and young adult male and female skeletons

Abstract: This study documents the timing of epiphyseal union at the innominate, femur, tibia, and fibula in a sample of modern Portuguese skeletons. The sample was taken from the Lisbon documented skeletal collection and it is comprised of 57 females and 49 males between the ages of 9 and 25. Individuals are mostly representative of the middle-to-low socioeconomic segment of the early 20th century Lisbon population. A total of 18 anatomical locations were examined for epiphyseal union using a three-stage scheme: 1) no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 25 publications
6
76
2
1
Order By: Relevance
“…15,53,84 Human remodeling rates range from 10% to 55% (average wholebody trabecular bone turnover per year 64 ), with age-associated cortical bone loss occurring primarily at the endocortical endosteum. 10 Bone adjacent to red marrow generally has higher rates of remodeling (eg, 10%-15% per year in ilium trabecular bone) compared with sites adjacent to yellow (fatty) marrow.…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…15,53,84 Human remodeling rates range from 10% to 55% (average wholebody trabecular bone turnover per year 64 ), with age-associated cortical bone loss occurring primarily at the endocortical endosteum. 10 Bone adjacent to red marrow generally has higher rates of remodeling (eg, 10%-15% per year in ilium trabecular bone) compared with sites adjacent to yellow (fatty) marrow.…”
Section: Developmentmentioning
confidence: 99%
“…Age Greater bone and cartilage healing ability in younger animals 15,57 Genetic background Strain variability, inbred vs outbred 34,43 Unlike the secondary bone present in the adult human long bone cortices, rodent long bone cortices are predominantly primary bone and have minimal cancellous bone available to harvest for autografts. 53 Bone growth in rats continues much longer after sexual maturity than in humans.…”
Section: Model Usesmentioning
confidence: 99%
“…11 On the other hand, mineralization of teeth is not affected as is their eruption by external factors, such as crowding, retention or early extraction of deciduous teeth, on the other hand, social, economic or malnutrition status may affect skeletal growth. [12][13][14] Most methods of age estimation in children evaluated mineralization of specific sets of teeth, most commonly mandibular. 15 Historically, maxillary teeth were not appropriate for radiologic analysis because of inferior appearance to mandibular teeth and superposition with corresponding skeletal structures on analog X-rays which is now mostly improved and corrected in digital radiography.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Regarding the epiphyseal union of the lesser tronchanter, Shama Y et al 7 reported that age of epiphyseal union of the lesser trochanter was 18-19 in male and women together. Cardoso 8 reported that the lesser trochanter at age of 14 of male showed nonunion.…”
Section: 24mentioning
confidence: 99%